Bridging organization design and performance : 5 ways to activate a global operating model - Kesler, Gregory, 1952-; Kates, Amy (Hoboken, New Jersey : Wiley, 2016)
Five practical steps to enhance organization effectiveness on a global scale. Bridging Organization Design and Performance is a handbook for leaders looking to enhance the success of their organizations and themselves. Companies that compete globally require organizational operating models as robust as their strategies. Many companies have created elegant designs and consider their worldwide, matrix organizations sources of competitive advantage. However, the reality is that these complex structures bring many challenges and senior executives are often frustrated by the difficulties of delivering growth in organizations that span numerous brands, products, and geographic regions. After working closely with over twenty large US and Europe based global companies during the past decade, Gregory Kesler and Amy Kates concluded that the problem is not in the fundamental design of these operating models. The matrix is not going away. The challenge is to effectively and completely activate the organization to deliver the strategy. This book shares the five practical actions that bring complex organizations to life and help companies gain sustainable results from their global operating models.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Organizational change; Organizational effectiveness; International business enterprises -- Management; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; International business enterprises -- Management; Organizational change; Organizational effectiveness; Electronic books